Differential Quadrature Method for solving the linear and nonlinear Klein - Gordon Equation - Hussein, Ahmed J. (University of Thi-Qar Journal of Science, 2019)
In this paper, numerical solution of Klein –Gordon equation is obtained by using differential quadrature method (DQM).This method is demonstrated by several examples. we compare the results with exact solution our results show this method is powerful and efficient for solve Klein –Gordon equation